(3ZfhI hMOhJIs (3GdaUd GdKGfjs - (3jhSa, YHO GdJhGHs; (3GdHWQhGj, YGOds ((3GdbGgQIs (3OGQ GdcJGH GdeUQjs, 2001)
(3eSQMjGJ ddCWaGd hGdfGTFIs
(3eSQMjGJ ddCWaGd hGdfGTFIs
1
Keywords: Arabic drama; (3GdeSQMjGJ GdYQHjIs